2020
DOI: 10.1016/j.heliyon.2020.e05126
|View full text |Cite
|
Sign up to set email alerts
|

Enforcement of legal remedies against construction projects time overrun in Ethiopia: A critical appraisal

Abstract: Construction time overrun is one of the common inefficiencies of public construction projects in Ethiopia. Laws and standard construction contracts stipulate different legal remedies against project time overrun. This paper is meant to unravel these legal remedies and their application to construction project time overrun in public construction projects in Ethiopia. To this end, the magnitude of time overrun, its common causes, and the practical implementation of legal remedies against it is exposed through li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…[12] and Sintayehu D.K. and T. Zhang (2020) call it construction project modes of contracting [41]. Despite the difference in terminology used by the above-enumerated authors, a common understanding that can be generated from them is that construction project delivery system is all about how the project participants are organized to transform the project owner's goals and objectives into finished products [40].…”
Section: Research Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…[12] and Sintayehu D.K. and T. Zhang (2020) call it construction project modes of contracting [41]. Despite the difference in terminology used by the above-enumerated authors, a common understanding that can be generated from them is that construction project delivery system is all about how the project participants are organized to transform the project owner's goals and objectives into finished products [40].…”
Section: Research Objectivementioning
confidence: 99%
“…649/2009 has developed its standard condition of contract to which several bid documents are attached with for procurement of non-complex works. For complex public works the value of which exceeds 10 million USD, government agencies in Ethiopia are instructed to make use of FIDIC standard contract forms [21,41]. This standard condition of contract is applicable only for DBB projects implemented by government agencies and the country has not yet developed a standard condition of contract to be used for other modes of contracting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Certain factors in the project execution generate negative results, such as deficient management and procedures in construction that result in delays at the beginning of the activities, reprocesses, inefficient planning and programming [4], and the lack of quality in materials and their slow delivery [5]. On the other hand, low productivity is one of the many challenges faced by the construction industry, which generates delays during the execution of the works [6]; therefore, this is the most significant challenge in construction [7]. Additionally, the Last Planner System is mentioned as a tool that is not being used properly due to certain deficiencies such as the absence of observation, incompatibilities with project delivery methods, inadequate planning, and non-compliance in the analysis of restrictions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tadewos and Patel [6] reported that none of the Addis Ababa highway projects were completed on time. Kebede and Zhang [7] also stated that one of the most common inefficiencies in the industry is the construction schedule delay. Zinabu [8] expressed concerns and recommended to take immediate actions for the reduction of construction schedule delays.…”
Section: Introductionmentioning
confidence: 99%
“…1 is calculated using Equation(7), and Table11presents the results computed for S i . S 1 = 0.128 + 0.147 + 0.122 + 0.086 + 0.169 + 0.145 + 0.120 + 0.120 + 0.240 + 0.188 + 0.189 = 1.654 4.…”
mentioning
confidence: 99%